Sex differences in pharmacokinetics of antidepressants - Kokras, N; Dalla, C; Papadopoulou-Daifoti, Z. (Expert Opin Drug Metab Toxicol, 2011)
INTRODUCTION: Sex differences have been identified in antidepressant treatment; however, it remains unclear to what extent pharmacokinetics contributes to these differences. As current antidepressant pharmacotherapy is less than optimal, understanding the role of sex in pharmacokinetics may substantially contribute to a gender-based optimized treatment. AREAS COVERED: An unrestricted PubMed literature search on antidepressant pharmacokinetics and sex was performed. Sex differences in absorption, distribution, metabolism and elimination of antidepressants, as well as the interaction of sex with age, genetic polymorphisms and gonadal hormones are discussed. We also provide an overview of how each antidepressant presents a particular sex-differentiated pharmacokinetic profile. Most antidepressants present to some extent pharmacokinetic sex differences, which often are further accentuated by gonadal hormones. In most cases, women, particularly elderly women, are expected to have higher exposure to antidepressants when dosed in a similar way as men. EXPERT OPINION: Although the available pharmacokinetic evidence indicates that women should receive lower doses of antidepressants and men should receive higher doses, current guidelines do not recommend dose adjustment, because these sex differences are considered to be clinically insignificant. Unless we understand the link between pharmacokinetics and pharmacodynamics of antidepressants, it will be difficult to determine whether sex differences are of clinical importance or not. Thus, further systematic and particularly focused research is needed on sex differences in pharmacokinetics.
Keywords: Aging; Antidepressive Agents/*pharmacokinetics/therapeutic use; Female; Gonadal Hormones/*metabolism; Humans; Male; Sex Characteristics